Microfluidic mazes to characterize T-cell exploration patterns following activation in vitro. Issue 11 (1st September 2015) - Jain, Namrata G.; Wong, Elisabeth A.; Aranyosi, Alexander J.; Boneschansker, Leo; Markmann, James F.; Briscoe, David M.; Irimia, Daniel
Abstract : We designed microfluidic maze devices to quantify the exploratory migration patterns of T-cells and found that mitogen activation and chemoattractant gradients significantly increase exploration patterns. Abstract : The migration of T-cell subsets within peripheral tissues is characteristic of inflammation and immunoregulation. In general, the lymphocyte migratory response is assumed directional and guided by local gradients of chemoattractants and/or chemorepellents. However, little is known about how cells explore their tissue environment, and whether lymphocyte activation may influence speed and exploratory patterns of migration. To probe migration patterns by T-cells we designed a microfluidic maze device that replicates critical features of a tissue-like microenvironment. We quantified the migration patterns of unstimulated and mitogen-activated human T-cells at single cell resolution and found significant differences in exploration within microfluidic mazes. While unstimulated lymphocytes migrated in a directed manner, activated T-cells migrated through large areas of the mazes in an exploratory pattern in response to the chemoattractants RANTES (CCL5) and IP-10 (CXCL10). The analysis of migration enabled by the microfluidic devices help develop new methods for determining how human circulating T-cells function in vivo to seek out antigens in health and disease states.